Prevalence and Characteristics of Pelvic Floor Dysfunction in a Tertiary Care Center in Indonesia: Prevalensi dan Karakteristik Disfungsi Organ Panggul di Pusat Pelayanan Kesehatan ersier diI ndonesia - Budi I Santoso; Nur R Fauziah (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To determine the prevalence and characteristics of pelvic floor dysfunction (PFD) in Jakarta, Indonesia. Methods: A cross sectional study was conducted at gynecology, endocrinology, and urogynecology clinic of Dr. Cipto Mangunkusumo Hospital during the period from January 2016 to April 2016. Subjects were selected using consecutive sampling. Data were taken using research and POP-Q form. Results: A total of 197 subjects were recruited. The prevalence of patients with PFD was 33%. The prevalence of POP, UI, and FI were 26.4%, 15.3% and 2.5%; respectively. Association between individual characteristics and PFD was found on women aged â‰¥ 60 and aged 40-59 years old with 69 and 14 times probability to be PFD. The probability of developing PFD was 76 and 14.2 times in multiparity and primiparity. Woman with vaginal delivery had a change to develop PFD 1.9 times and postmenopausal woman had a probability 18 times. The infuencing risk factor in PFD were age parity, race, mode of delivery, and menopausal status. Conclusion: Pelvic floor dysfunction affects a substantial of women and increases with age, parity and aging. [Indones J Obstet Gynecol 2017; 5-3: 168-172] Keywords: fecal incontinence, pelvic floor dysfunction, pelvic organ prolapse, urinary incontinence